Odpowiedź :
nie będę przepisywać jeszcze raz tylko od razu po znaku = hahah
a) - 2x + 6xy + 4x - y = 2x - y + 6xy
b) k + 2k + 8m - 3km = 3k + 8m - 3km
c) - 6xy - 2xy + 3x - 4y = - 8xy + 3x - 4y
d) 9a + 4c - 8c + 2a = 11a - 4c
e) - 3t - w - t + 2w = w - 4t
f) -3x - 1 + 6x + 2 = 3x + 1
powodzonka i miłej nocy :))
a) - 2x + 6xy + 4x - y = 2x - y + 6xy
b) k + 2k + 8m - 3km = 3k + 8m - 3km
c) - 6xy - 2xy + 3x - 4y = - 8xy + 3x - 4y
d) 9a + 4c - 8c + 2a = 11a - 4c
e) - 3t - w - t + 2w = w - 4t
f) -3x - 1 + 6x + 2 = 3x + 1
powodzonka i miłej nocy :))
Odpowiedź:
a) -2x+(6xy+4x-y)=-2x+6xy+4x-y=2x+6xy-y
b)k+(2k+8m-3km)=k+2k+8m-3km=3k+8m-3km
c)-6xy-(2xy-3x+4y)=-6xy-2xy+3x-4y=-8xy+3x-4y
d)9a+4c-(8c-2a)=9a+4c-8c+2a=11a-4c
e)-(3t+w)-(t-2w)=-3t-w-t+2w=2t+w
f)-(3x+1)+(6x+2)=-3x-1+6x+2=3x+1\
liczę na naj
Szczegółowe wyjaśnienie: